Metabolites Secreted by a Plant-Growth-Promoting Pantoea agglomerans Strain Improved Rooting of Pyrus communis L. cv Dar Gazi Cuttings - Luziatelli, Francesca; Gatti, Lorenzo; Ficca, Anna Grazia; Medori, Gabriele; Silvestri, Cristian; Melini, Francesca; Muleo, Rosario; Ruzzi, Maurizio (Frontiers in Microbiology, 2020)
Strains belonging to Pantoea agglomerans species are known for their ability to produce metabolites that can act in synergy with auxins to induce the adventitious root (AR) formation. The latter is critically important in the agamic propagation of several woody species, including pear (Pyrus communis L.), playing a considerable role in the commercial nursery farms including those using micropropagation techniques. When grown on a medium amended with tryptophan, the plant growth-promoting (PGP) strain P. agglomerans C1 produces a cocktail of auxin and auxin-like molecules that can be utilized as biostimulants to improve the rooting of vegetable (Solanum lycopersicum L.), and woody crop species (Prunus rootstock GF/677 and hazelnut). In this study, we evaluated the morphological and molecular responses induced by strain C1 exometabolites in microcuttings of P. communis L. cv Dar Gazi and the potential benefits arising from their application. Results showed that exometabolites by P. agglomerans C1 induced a direct and earlier emergence of roots from stem tissues, and determined modifications of root morphological parameters and root architecture compared to plants treated with the synthetic hormone indole-3-butyric acid (IBA). Transcription analysis revealed differences in the temporal expression pattern of ARF17 gene when IBA and C1 exometabolites were used alone, while together they also determined changes in the expression pattern of other key auxin-regulated plant genes. These results suggest that the phenotypic and molecular changes triggered by P. agglomerans C1 are dependent on different stimulatory and inhibitory effects that auxin-like molecules and other metabolites secreted by this strain have on the gene regulatory network of the plant. This evidence supports the hypothesis that the strategies used to harness the metabolic potential of PGP bacteria are key factors in obtaining novel biostimulants for sustainable agriculture. Our results demonstrate that metabolites secreted by strain C1 can be successfully used to increase the efficiency of micropropagation of pear through tissue culture techniques.